Lactobacillus plantarum-derived extracellular vesicles from dietary barley leaf supplementation attenuate Citrobacter rodentium infection and intestinal inflammation - Yu Feng; Qian Zhao; Yifan Zhao; Chen Ma; Meiling Tian; Xiaosong Hu; Fang Chen; Daotong Li (Journal of Nanobiotechnology)
Abstract Background Inflammatory bowel disease (IBD) is a gastrointestinal inflammatory disorder characterized by disturbed interactions between gut microbiota and host immune response. Barley leaf (BL) is a traditional Chinese herb recorded to have health-promoting effects. However, little is known about the beneficial role of BL against enteric infection-induced intestinal inflammation. Here, we uncover that BL protects against Citrobacter rodentium (C. rodentium)-induced infectious colitis by improving host-microbiota interactions. Methods C3H/HeN mice were fed a diet with/without BL and infected with C. rodentium. Transcriptome sequencing, anti-CD4 antibody treatment, and flow cytometry were conducted to investigate the mechanisms of T cell immune modulation. The intervention involved administering anti-CD4 antibody at 500 µg each time for three times before and during C. rodentium infection. Analysis of gut microbiota composition was performed by 16S rRNA gene sequencing on fecal samples. Fecal microbiota transplantation was conducted by administering microbiota from donor group to recipient group via oral gavage to investigate the role of intestinal microbiota in immune modulation. Results BL ameliorated the severity of C. rodentium-induced colitis, and this effect was linked to improved gut homeostasis and enhanced mucosal barrier function. BL enriched the pathways of T helper 1 (Th1)/Th2 and Th17 cell differentiation in the colon, suggesting the involvement of CD4+ T cells. Consistent with this, anti-CD4 antibody treatment abrogated the effect of BL and flow cytometry analysis revealed that BL mitigated C. rodentium-induced pro-inflammatory Th1 immune response. Moreover, the protective effect of BL was associated with alleviation of gut microbiota dysbiosis and increased abundance of Lactobacillus. Our in vivo studies further revealed that live Lactobacillus plantarum (L. plantarum) administration attenuated the pathogenic effects induced by C. rodentium infection, whereas heat-inactivated L. plantarum did not show the same results. Mechanistically, BL supplementation enriched L. plantarum, which subsequently released nanosized extracellular vesicles (EVs) that serve as a key mediator in alleviating C. rodentium-associated pathology and Th1 cell dysregulation. Conclusions Our work thus provides evidence for utilizing BL and L. plantarum-derived EVs to manage enteric infection-associated IBD.